Cultivation, evaluation of the anticancer activities and assessment of the phylogenetic selected strain of Chlorella vulgaris and Spirulina platensis / Mohd Syahril Mohd Zan, Roshani Othman and Nur Hasyimah Ramli - Mohd Zan, Mohd Syahril; Othman, Roshani; Ramli, Nur Hasyimah (Research Management Institute (RMI), 2012)
Cyanobacteria are photosynthetic organisms with relatively simple requirements for growth, when compared to other sources of biomass. The carbon source necessary for the cultivation of cyanobacteria represents up to 60% of the costs with nutrients. The cynanobacteria also are one of the richest sources of biomedically relevant compounds with extensive therapeutic pharmaceutical applications (Gademann & Portman, 2008). Cyanobacteria metabolites show an interesting and exciting range of biological activities ranging from antimicrobial, immunosuppressant, anticancer and antiviral to proteinase-inhibiting activities which are striking targets of biomedical research (Luesch et al., 2002). Chemotherapy is one of the main treatments used to cure cancer. A great number of antitumor compounds are natural products or their derivatives, mainly produced by blue-green algae (Patterson et al, 1991, 1993). This study will be focus with an alternative treatment to produce new anticancer-type natural products from cyanobacteria. The proposed project will be focused on the isolation and purification of microalgae from natural habitat. Various culture media will be developed and modified such as AF6 medium (Watanabe et al., 2000), AK medium (Barsanti & Gualtieri, 2006), COMBO medium (Kilham et al., 1998) and Medium G (Blackburn et al., 2001) for isolation and cultivation of microalgae. The molecular-based techniques will be developed in monitoring, identification and quantification of microalgae species in mixed phytoplankton samples. The targets cyanobacteria will be growing rapidly are further subcultured and grow to a density sufficient for inoculation of scale-up volume. After cell densities of the scaled-up cultures are harvested, the cell material is freeze dried. The biomass is extracted using pure chloroform to obtain a crude lipid extract. This extracts will be evaluated for anticancer-type activity by using MTT assay. The standard chemotherapeutic agent doxorubicin will be used as a positive control in MTT assay and normal cell line L02 will be used to show whether cytotoxic activity was tumor-specific. The concentrations required to inhibit growth by 50% (IC50) will be calculated from survival curves using the Bliss method. This studies are to known the potential of cyanobacteria as anticancer and to screen cyanobacteria products for anticancer activity by MTT assay. It more to organic and new anticancer-type natural products which have no harmless to normal human cells.